RETRACTED: Modeling the properties of new potential modifiers of the medium for cryopreservation of fish sperm - Kolyada Margarita; Pashchenko Konstantin; Osipova Victoria; Abakumova Ekaterina; Velikorodov Anatoly (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001